KEAMANAN PENGGUNAAN ANESTESI REGIONAL PADA PERSALINAN PENGIDAP HIV - Kumaat, Lucky (UNIVERSITAS SAM RATULANGI, 2010)
Abstract: Human Immunodeficiency Virus (HIV) infection and Acquired Immunodeficiency Syndrome (AIDS) are the major problems of global health. It is estimated that approximately 75.9% of Human Immunodeficiency Virus (HIV)-infected women aged are in productive ages (20-39 years) with possibilities to become pregnant. Since the prevalence of Human Immunodeficiency Virus infection in pregnant women is increasing, anesthesiologists are increasingly confronting these diseases in their patients. HIV infection in pregnant women often raises questions about the safety of regional anesthesia for them. Fears of the spread of infection to the Central Nervous System (CNS) or the sequel of the neurological system have led some clinicians not to use regional anesthesia. Some research shows that pregnant women with HIV infection are not a contraindication for regional anesthesia since there is no CNS and neurological sequel or infection after a long enough time post operation. Keywords: HIV infection, AIDS, parturition, regional anaesthesia.Â Abstrak: Infeksi Human Immunodeficiency Virus (HIV) dan Acquired Immunodeficiency Syndrome (AIDS) adalah masalah utama dari kesehatan global. Diperkirakan sekitar 75,9% wanita yang terinfeksi HIV berada pada usia produktif (20-39 tahun) yang berpeluang untuk hamil. Karena prevalensi infeksi HIV pada wanita hamil semakin meningkat, maka ahli anestesi semakin banyak diperhadapi dengan pasien demikian. Infeksi HIV pada wanita hamil seringkali memunculkan pertanyaan mengenai keamanan penggunaan anestesi regional pada mereka. Kekuatiran terhadap penyebaran infeksi ke sistim susunan saraf pusat (SSP) atau sekuel neurologik menyebabkan sebagian klinisi menentang penggunaan anestesi regional. Beberapa penelitian telah membuktikan bahwa wanita hamil dengan HIV bukan merupakan kontraindikasi bagi penggunaan anestesi regional karena tidak dijumpai adanya infeksi SSP atau sekuel neurologik setelah selang waktu yang cukup panjang pasca operasi. Kata kunci: Infeksi HIV, AIDS, persalinan, anestesi regional.